Two Identical Twin Nitrogen Mustard Agents that Express Rapid Alkylation Activity at Physiological pH 7.4 and 37°C - Bartzatt, Ronald; Donigan, Laura (Letters in Drug Design & Discovery, 2004)
Two nitrogen mustard (N-mustard ) agents were synthesized utilizing ethylene diamine and hexane diamine as the parent compounds. These N-mustard agents were solids at 25o C and stable while stored dry at -10°C. The two N-mustards assumed the configuration of identical twin drugs which when placed in aqueous solution were highly reactive. Both N-mustards were soluble in aqueous NaHCO3 buffer and expressed alkylation activity directed towards a nucleophilic primary amine target (4-chloroaniline) at blood pH 7.4 and 37°C. Utilizing the fluorescent probe fluorescamine, which is highly specific for primary amines, the quantity of unreacted nucleophilic 4-chloroaniline remaining after a known time period was determined. This enabled the calculation of rate constants and the determination of rate equation for alkylation to be first-order for N,N,N',N'-tetrakis(2-chloroethyl)ethane-1,2-diamine and zero-order for N,N,N',N'- tetrakis(2-chloroethyl)hexane-1,6-diamine. Molecular property descriptors such as Log P, parachor, molar volume, molar refractivity, dipole, molecular volume & area, and polar surface area were calculated for comparison. Zero violations of the Rule of 5 indicates these two mustard agents will have good bioavailability and good bioactivity.
Keywords: identical twin drug